The morphological and chemical properties of fine roots respond to nitrogen addition in a temperate Schrenk’s spruce (Picea schrenkiana) forest - Haiqiang Zhu (Nature Portfolio, 2021)
Abstract Fine roots (< 2 mm in diameter) play an important role in belowground ecosystem processes, and their physiological ecology is easily altered by nitrogen deposition. To better understand the response of physiological and ecological processes of fine roots to nitrogen deposition, a manipulation experiment was conducted to investigate the effects of exogenous nitrogen addition (control (0 kg ha−1 a−1), low (5 kg ha−1 a−1), moderate (10 kg ha−1 a−1), and high nitrogen (20 kg ha−1 a−1)) on the biomass, morphological characteristics, chemical elements and nonstructural carbohydrates of fine roots in a Picea schrenkiana forest. We found that most fine roots were located in the 0–20 cm of soil layer across all nitrogen treatment groups (42.81–52.09% of the total biomass). Compared with the control, the biomass, specific root length and specific root area of the fine roots increased in the medium nitrogen treatment, whereas the fine roots biomass was lower in the high nitrogen treatment than in the other treatments. In fine roots, nitrogen addition promotes the absorption of nitrogen and phosphorus and their stoichiometric ratio, while reducing the content of nonstructural carbohydrates. The content of nonstructural carbohydrates in the small-diameter roots (< 1 mm in diamter) in each nitrogen treatment group was lower than that in the large-diameter roots. Correlation analysis showed that soil carbon and nitrogen were positively correlated with fine root biomass and specific root length and negatively correlated with the nonstructural carbohydrates. Our findings demonstrate that medium nitrogen addition is conducive to the development of fine root morphology, while excessive nitrogen can suppress the growth of root systems.